Pengembangan Media Pembelajaran Interaktif Pada Materi Bangun Ruang Sisi Datar Kelas VIII SMP Al-Azhar 3 Bandar Lampung Tahun Pelajaran 2021/2022 - Amatullah, Duta Cendikia; Sutrisno AB, Joko (STKIP PGRI Bandar Lampung, 2022)
This research and development aims to (1) produce and develop products in the form of interactive learning media on flat-sided building materials for class VIII students of SMP Al-Azhar 3 Bandar Lampung (2) Knowing the quality of products in terms of validity as learning media and the effectiveness of using learning media products interactive material on flat-sided space construction for class VIII SMP Al-Azhar 3 Bandar Lampung. The procedure of this research is development research using the ADDIE development model with 5 stages carried out namely analysis, design, development, implementation, and evaluation. student response questionnaires and student evaluation tests. Interactive media validation is carried out by 6 expert lecturers who are competent in their fields. Then this interactive media was tested on class VIII students of SMP Al-Azhar 3 Bandar Lampung, and then the students responded through the response questionnaires given. The results of the validation of material experts on aspects of learning and content obtained a score of 69% with valid criteria. Media expert validation on aspects includes the display of specifications that get a value of 92% with very valid criteria. The validation of linguists on aspects of sentence structure determination and understanding of messages and information obtained a value of 100% with very valid criteria. After using the developed interactive media, students' learning mastery can be categorized as very good with the achievement of classical mastery of 95%, thus interactive media for class VIII is suitable for use as teaching materials.